Assessing thermal behaviors and kinetics of (co-)combustion of textile dyeing sludge and sugarcane bagasse. (25th February 2018) - Xie, Wenhao; Huang, Jianli; Liu, Jingyong; Zhao, Yongjiu; Chang, Kenlin; Kuo, Jiahong; He, Yao; Sun, Jian; Zheng, Li; Xie, Wuming; Sun, Shuiyu; Buyukada, Musa; et al.
Highlights: Co-combustion performance of textile dyeing sludge & sugarcane bagasse was assessed. Positive interaction effects occurred with the co-combustion. Evolved-gas-analysis was quantified using TG-MS. Blended samples evolved less SO2 but more NOx, NH3 and CO2 emissions. Ea estimates by FWO and KAS showed lower activation energy for blended samples. Abstract: Thermogravimetric and mass spectrometric (TG-MS) experiments were carried out using textile dyeing sludge (TDS), sugarcane bagasse (SB) and their blends with different ratios. (Co-)combustion kinetic parameters of each sample were calculate by using TG-derivative curves. CO2, NOx, NH3 and SO2 emissions were also quantified. The addition of SB to TDS lowered SO2 but enhanced NOx, NH3 and CO2 emissions. Calculated activation energies ( E ) of the pure TDS and SB, and their blend (TB64) according to the Flynn-Wall-Ozawa method were on average in the range of 185.6–253.9 kJ·mol −1, 152.9–235.9 kJ·mol −1 and 111.1–161.8 kJ·mol −1, respectively. Based on the Kissinger-Akahira-Sunose method, E estimates of the pure TDS and SB, and the blend ranged from 183.1 to 251.0 kJ·mol −1, 152.1 to 237.2 kJ·mol −1 and 108.2 to 160.1 kJ·mol −1, respectively. Our results indicated that the blend E was affected by the interactions between TDS and SB.